PENGARUH TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN DENGAN INSTITUTIONAL OWNERSHIP SEBAGAI VARIABEL MODERASI - Dewi Kusuma Wardani; Ria Herawati (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
One of the factors that can affect the value of the company is tax avoidance. This tax avoidance effort is carried out by reducing the tax burden. However, the existence of institutional investors is considered capable of being an effective monitoring mechanism in every decision taken by managers. The results of research that have been conducted on 21 manufacturing companies listed on the IDX for the period 2016-2020 show that tax avoidance has a positive effect on firm value and institutional ownership is able to moderate the negative effect of tax avoidance on firm value